Characterization of gallic acid-Chinese yam starch biodegradable film incorporated with chitosan for potential use in pork preservation. (February 2023) - Rong, Liyuan; Ji, Xiaoyao; Shen, Mingyue; Chen, Xianxiang; Qi, Xing; Li, Yulin; Xie, Jianhua
Graphical abstract: Highlights: Gallic acid (GA)-induced starch film was prepared incorporated with chitosan (CS). GA and CS increased the mechanical, antibacterial, antioxidant properties of films. GA/YS/CS films can effectively improve the quality of pork during storage. Abstract: The widely use of petroleum-based plastics causes serious environmental pollution and oil resource shortage. In this work, biodegradable films were prepared based on gallic acid (GA)-induced Chinese yam starch (YS) and chitosan (CS). The fresh-keeping effect of biodegradable films on the pork meat preservation were investigated. The prepared GA/YS/CS biodegradable films exhibited thinner thickness and better light transmittance, because CS effectively decreased the viscosity of film-forming solution and weaken its internal link structure. The SEM results and mechanical results revealed that the YS, GA, and CS had a good compatibility, GA modification and adding CS markedly improved the tensile strength of YS-based film, because the interaction between CS and starch molecular was facilitate owing to the NH3 + of CS tended to form hydrogen bonds with the hydroxyl group of starch. Sensory analysis results suggested that GA/YS/CS films can effectively improve the quality of pork during storage compared to the package of polyethylene film. In summary, the prepared GA/YS/CS film in this work had practical application potential in pork preservation due to its excellent mechanical, antibacterial, oxidation resistance properties, and the development and application of biodegradable starch film can greatly reduce the increasingly serious environmental pollution pressure.